Application of index Kerdo in practice of physical rehabilitation. - Afanasieva O.V; Evdokimov E.I (Kharkov National Pedagogical University, 2011)
The possibility of using the simple methods of monitoring the effectiveness of physiotherapy and physical rehabilitation methods in treatment of children with acute pneumonia is examined. In research were involved 26 adolescents aged 12 -17 years with acute pneumonia. It is shown that there is a strong correlative relationship between indicators of respiratory function and vegetovascular equilibrium. It is suggested the use in daily practice of physical rehabilitation calculating of public criteria - according to Kerdo index for monitoring the effectiveness of treatment.